"Staying in the Game": How Procedural Variation Shapes Competence Judgments in Surgical Education. (November 2016) - Apramian, Tavis; Cristancho, Sayra; Watling, Chris; Ott, Michael; Lingard, Lorelei
Abstract : Purpose: Emerging research explores the educational implications of practice and procedural variation between faculty members. The potential effect of these variations on how surgeons make competence judgments about residents has not yet been thoroughly theorized. The authors explored how thresholds of principle and preference shaped surgeons' intraoperative judgments of resident competence. Method: This grounded theory study included reanalysis of data on the educational role of procedural variations and additional sampling to attend to their impact on assessment. Reanalyzed data included 245 hours of observation across 101 surgical cases performed by 29 participants (17 surgeons, 12 residents), 39 semistructured interviews (33 with surgeons, 6 with residents), and 33 field interviews with residents. The new data collected to explore emerging findings related to assessment included two semistructured interviews and nine focused field interviews with residents. Data analysis used constant comparison to refine the framework and data collection process until theoretical saturation was reached. Results: The core category of the study, called staying in the game, describes how surgeons make moment-to-moment judgments to allow residents to retain their role as operators. Surgeons emphasized the role of principles in making these decisions, while residents suggested that working with surgeons' preferences also played an important role in such intraoperative assessment. Conclusions: These findings suggest that surgeons' and residents' work with thresholds of principle and preference have significant implications for competence judgments. Making use of these judgments by turning to situated assessment may help account for the subjectivity in assessment fostered by faculty variations.